La dignidad humana y el derecho a la salud de las personas privadas de libertad en los centros de rehabilitación social del Ecuador - Pazán, María A. (2020)
The aim of this research is to identify human dignity and the right to health of persons deprived of their liberty in social rehabilitation centres. From a perspective where the national legislation and international treaties protecting persons deprived of their liberty are analyzed, defining in doctrine the concept of dignity and the fundamental value it possesses for the dignity of all rights, in the set of rights that the person deprived of liberty possesses, regardless of whether his situation is one of deprivation of liberty. The World Health Organization states that the entire state of the human being is the optimal physical, mental and social well-being, despite existing legislation in Ecuador, the right to health is affected. Considering health as the set of basic goods necessary for the individual to develop his potentialities; the concepts of quality of life, dignity and health are correlated to give rise to an effective enjoyment of all other related rights. The special protection of the right to health to be adopted by States parties to conventions and treaties to ensure the prevention and treatmentof diseases of persons deprived of their liberty.